Expansão da EAD sob a ótica da difusão da inovação: um estudo sobre universidades corporativas do setor público da Bahia - VALE JUNIOR, João Sotero do (2017)
The advent of new Information Technologies (ICTs) has been causing changes in the socioeconomic and educational sectors, among others. Over the years, we are experiencing structural changes in the teaching-learning process based on new ICTs, through distance education (EAD). The general objective of this study was to evaluate the technological trajectory, constraints and impacts of the process of diffusion of the EAD technology in large public organizations of the State of Bahia. At the theoretical-methodological level, the research develops an approach based on concepts established in the field of diffusion of innovation, which make it possible to understand and analyze the EAD as one of the emerging technologies of the current technological revolution. In this way, it was possible to describe and analyze aspects such as the technological trajectory, the organizational arrangements, the conditioning factors and the impacts of the EAD diffusion in the researched entities. It is a descriptive and exploratory study of a qualitative nature. It has as empirical object the Corporate Public Service Universities (UCSs) of the State Treasury Secretariat (SEFAZ-BA) and the Bahian Water and Sanitation Company (EMBASA), having as main source of information managers responsible for the EAD area of ​​the institutions. Data were collected through interviews, observation and analysis of institutional documents. The Analysis Model was established based on the literature review on diffusion of innovation and EAD, with customizations made by the author to the specific object of the research. The results indicate a slow process of diffusion of the EAD technology and limitations related to the format of the courses and the scope of their reach in the studied organizations, and they identify difficulties to obtain the specialized technical resources necessary to advance the EAD programs. The mobilization of the innovation diffusion theory approach has proved to be profitable, generating a comprehensive understanding of the path of the EAD diffusion process and the identification of crucial points for the improvement of the corporate education strategy (CE) in the organizations studied.